Кераміка з розкопок Березані в збірці Національного музею історії України - Пукліна, О.О.; Буйських, А.В. (Археологія, 2010)
Вводиться до наукового обігу керамічна колекція з розкопок давньогрецького поселення на о. Березань, що зберігається
в Національному музеї історії України. Вводится в научный оборот небольшая коллекция античной расписной керамики, найденной на о. Березань
и хранящейся в собрании Национального музея истории Украины. Она состоит из частных пожертвований, а
также материалов из раскопок под руководством Э.Р. Штерна и М.Ф. Болтенко, переданных в музей в 1946 г.
Абсолютное ее большинство представлено фрагментами североионийской посуды открытых и закрытых форм —
кратеров, столовых амфор, ойнохой, тарелок и блюд, а также ионийских киликов первой половины VI в. до н. э.
Имеются фрагменты хиосских столовых сосудов того же времени — кубков и чаш, а также коринфских — скифоса
и арибалла. Южноионийская посуда — это фрагменты столовых амфор стиля Фикеллура второй половины VI в.
до н. э. Публикуемая коллекция дополняет современные представления о составе березанских находок, отражая
основные направления керамического импорта в VI в. до н. э. A small collection of Ancient Greek painted ceramics found on Berezan Island and kept in the collection of the National
Museum of History of Ukraine is presented for publishing. It contains private donations as well as materials from excavations
under the supervision of E.R. Šhtern and M.F. Boltenko passed to the Museum in 1946. The absolute majority of it is
represented by the fragments of the North Ionian opened and closed vessels: krateres, table amphorae, oinochoai, dishes and
plates, and also Ionian cups of the first half of the 6th c. BC. There are fragments of Chiot tableware of the same period: of cups
and bowls, and also of Corinthian vessels: of a skythos and an aryballos. The South Ionian vessels include fragments of table
amphorae of Fikellura style of the second half of the 6th c. BC. The published here collection contributes to the contemporary
knowledge on the structure of finds from Beresan, representing the main ways of ceramics import in the 6th c. BC.